SISTEM PENDUKUNG KEPUTUSAN PENCARIAN RESTORAN DI YOGYAKARTA SESUAI KEBUTUHAN KONSUMEN MENGGUNAKAN METODE WEIGHTED PRODUCT - Yofy Mandasari; Anton Setiawan Honggowibowo; Dwi Nugraheny (Compiler, 2013)
Decission Support System or DSS is a system thath help managers to solve a semi-structured problem. There are techniques used to make the DSS, one of them is Fuzzy Logic Multi-Attribute Decission Making (MADM). Weighted Product is a method to solve the problems using multiplication to connect the attribute ratings, where the rating attributes must be raised first with the weight of therelevant attributes. The application results show that the system can assist the consumer in deciding the restaurant according to the criteria. In addition, this application can also shorten the time in search of existing restaurants in Yogyakarta.